Determinant of Financial Literacy on Indonesian Migrant Employees in Malaysia - Achmad Rizal; Adib Susilo; U’um Munawaroh; Fadhilah Abdullah Asuhaimi; Aris Munandar (Universitas Muhammadiyah Malang, 2023)
Malaysia is the main destination for Indonesian migrant employees to work aboard. This research aims to investigate the factors influenced financial literacy of Indonesian Migrant Employee in Malaysia. Ordered Logistic Regression is employed in this research in order to conduct a survey among 303 Indonesian Migrant Workers. OLS model employed to test the effect of financial attitude, financial behavior, financial knowledge, financial socialization, and demographic variables on the financial literacy. The result found that financial attitude, financial behavior and financial socialization have positive and statistically affects on the financial literacy. Meanwhile, in term of age, participants at 36-50 years old have positively and statistically affects on the financial literacy, while senior and diploma students have a higher financial literacy in terms the level of education. In addition, Gender also have positively and statistically effects on financial literacy. This study contributes to increase the discourse of financial literacy especially in financial knowledge that needs to be improved by government for Indonesian employee.